Single-cell sequencing elucidates the mechanism of NUSAP1 in glioma and its diagnostic and prognostic significance - Meng-Yu Zhao; Zhao-Lei Shen; Hongzhen Dai; Wan-Yan Xu; Li-Na Wang; Yu- Gu; Jie-Hui Zhao; Tian-Hang Yu; Cun-Zhi Wang; Jia-feng Xu; Guan-Jun Chen; Dong-Hui Chen; et al. (Frontiers in Immunology)
BackgroundPersonalized precision medicine (PPPM) in cancer immunology and oncology is a rapidly advancing field with significant potential. Gliomas, known for their poor prognosis, rank among the most lethal brain tumors. Despite advancements, there remains a critical need for precise, individualized treatment strategies.MethodsWe conducted a comprehensive analysis of RNA-seq and microarray data from the TCGA and GEO databases, supplemented by single-cell RNA sequencing (scRNA-seq) data from glioma patients. By integrating single-cell sequencing analysis with foundational experiments, we investigated the molecular variations and cellular interactions within neural glioma cell subpopulations during tumor progression.ResultsOur single-cell sequencing analysis revealed distinct gene expression patterns across glioma cell subpopulations. Notably, differentiation trajectory analysis identified NUSAP1 as a key marker for the terminal subpopulation. We found that elevated NUSAP1 expression correlated with poor prognosis, prompting further investigation of its functional role through both cellular and animal studies.ConclusionsNUSAP1-based risk models hold potential as predictive and therapeutic tools for personalized glioma treatment. In-depth exploration of NUSAP1’s mechanisms in glioblastoma could enhance our understanding of its response to immunotherapy, suggesting that targeting NUSAP1 may offer therapeutic benefits for glioma patients.